Does Halal Tourism Matter? A Study About Implementation of Sharia-based Hotel in Bandung, West Java, Indonesia - Syara, Ajeung Syilva; Fauzan, Tribowo Rachmat (Fakultas Syariah INSURI Ponorogo, 2023)
Background. Halal tourism is a significant concern in Indonesia, where most people are Muslim. One of the halal tourism industry sectors that has emerged in society is the existence of Sharia-based hotels. Sharia hotels are hotels whose management is in accordance with Sharia principles. However, only a few hotels in Bandung use Sharia principles because there are no standard regulations for halal tourism. Purpose. The purpose of this research is to understand the juridical regulations regarding the sharia-principle hotel industry and to understand the level of public awareness and compliance in utilizing services in the Sharia hotel industry in the city of Bandung. The research methodology used is normative juridical, using empirical juridical research of a qualitative nature, using empirical normative legal research methods. The Sharia hotel industry is still implementing the Minister of Tourism and Creative Economy Regulation No. 2 of 2014 concerning Guidelines for the Implementation of Sharia Hotel Business; there is a legal vacuum here because juridically, the rules and regulations regarding Sharia hotels have not been made or do not yet exist. Conclusions is the hotel with a Sharia concept is a good intention from the stakeholders of the Sharia economy. In Bandung, there are several Sharia hotels that have not been certified but have implemented Sharia principles in their management, so these hotels have carried out independent assessments, so they are permissible as long as they do not conflict with Islamic values as empirical evidence of the theory of legal personality